2018
DOI: 10.1016/j.surfcoat.2017.11.051
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced corrosion and wear resistance properties of carbon fiber reinforced Ni-based composite coating by laser cladding

Abstract: To enhance the wear resistance and corrosion resistance of Ni-based coatings, carbon fibers reinforced nickel-based composite coatings (CFs/Ni) were fabricated on the surface of 1Cr13 stainless steel by laser cladding (LC). The microstructure characteristics, microhardness, wear and corrosion performances of the composite coatings were investigated. The results show that CFs can effectively improve the corrosion and wear resistances of Ni-based coatings. With increasing laser scanning speed, the morphology of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
64
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 203 publications
(64 citation statements)
references
References 48 publications
(38 reference statements)
0
64
0
Order By: Relevance
“…The authors of [11] demonstrated an innovative approach for controlling the surface topography and tribological behavior of biomedical alloys, such as Ti6Al4V, by means of electron beam surface treatment. Other researchers [12,13] have successfully demonstrated the possibilities for enhancing the wear and corrosion properties of steel by the formation of carbon fiber-reinforced Ni-based composite coatings via laser cladding. Laser beam technologies have a large number of applications in the field of modern medicine and are extensively discussed in [10].Other methods for coating deposition are plasma spray technologies, physical vapor deposition (PVD), etc.…”
mentioning
confidence: 99%
“…The authors of [11] demonstrated an innovative approach for controlling the surface topography and tribological behavior of biomedical alloys, such as Ti6Al4V, by means of electron beam surface treatment. Other researchers [12,13] have successfully demonstrated the possibilities for enhancing the wear and corrosion properties of steel by the formation of carbon fiber-reinforced Ni-based composite coatings via laser cladding. Laser beam technologies have a large number of applications in the field of modern medicine and are extensively discussed in [10].Other methods for coating deposition are plasma spray technologies, physical vapor deposition (PVD), etc.…”
mentioning
confidence: 99%
“…Carbon fiber has high strength, high modulus, and low expansion properties, which is a common reinforcement in composites . Carbon fiber can significantly improve the tensile strength, corrosion, and wear resistance of Ni‐based composite coatings, according to previous studies . In addition, there is no solid solubility between the C‐element and many other elements.…”
Section: Introductionmentioning
confidence: 98%
“…A large number of metal-based composite coatings had been synthesized on different metals and alloys. Lei et al [10] prepared carbon fiber reinforced nickel-based composite coatings on the surface of 1Cr13 stainless steel by laser cladding. Compared withthe coating without carbon fibers,the hardness of the coatings with 6 vol.% carbon fibers was increased by 30%.…”
Section: Introductionmentioning
confidence: 99%